Incidencia de la lectura en la comunicación oral y escrita de los estudiantes del tercer año de bachillerato de la unidad educativa anexa a la Universidad Nacional de Loja, periodo lectivo 2012-2013 - Moreno Romero, Diego Andrés (2014)
This research work has been titled “IMPACT OF READING IN THE ORAL AND WRITTEN COMMUNICATION STUDENT OF THIRD YEAR OF BACHELOR OF EDUCATION UNIT ATTACHED TO THE UNIVERSITY OF Loja, LECTIVO PERIOD,2012-2013”. To which the following overall goal "Check how reading really affects oral and written communication students of the Third Year Bachelor of Education Unit Attached to the National University of Loja, academic year 2012-2013." was formulated. Within the methodology consists scientific , inductive - deductive method , synthetic and have also used the techniques and most relevant instruments , such as the literature review documentary , surveys of teachers and students , for which he worked with a population 80 Third Year students and 7 Teachers High School Area Language and Literature. Among the main results , has established the following conclusions ; reading significantly affects oral and written communication, by the fact that teachers and students believe that reading is essential basis within their academic process , because it improves their vocabulary , their cultural heritage , their ability to function in a social setting. In written communication reading improves writing, accuracy in the expression of ideas, and helps to have a good speller. It was determined that he was not devoted the time to read that for a teenager is 60 to 90 minutes a day as manifested Pedro Lain Entralgo also be able to conclude 5 that the choice of texts by students is not adequate for personal development, and that there is adequate motivation of teachers to promote reading activity. In view of this, the following recommendations are proposed that teachers should participate actively in the formation processes of reading in students also organize workshops, lectures, book clubs , speech contests , writing workshops creation conversations with parents to form this habit from an early age. With this work the impact that counts reading in oral and written communication students explained; guidelines and strategies to embed students in time and the choice of appropriate training texts as readers and get them to give him the true importance of reading in the formation of the students raised.